2014
DOI: 10.1603/me13152
|View full text |Cite
|
Sign up to set email alerts
|

Somatic <I>Wolbachia</I> (Rickettsiales: Rickettsiaceae) Levels in <I>Culex quinquefasciatus</I> and <I>Culex pipiens</I> (Diptera: Culicidae) and Resistance to West Nile Virus Infection

Abstract: The endosymbiotic bacteria Wolbachia pipientis Hertig infects a wide variety of insect species and can increase viral resistance in its host. Wolbachia naturally infects Culex quinquefasciatus Say and Culex pipiens L. mosquitoes, both vectors of West Nile virus (WNV). We recently demonstrated that Wolbachia infection of Cx. quinquefasciatus laboratory strain Ben95 increases host resistance to WNV infection, reducing vector competence. This observation raised the possibility that Wolbachia could impact vector c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 62 publications
0
52
0
3
Order By: Relevance
“…Additionally, the high abundance of Pseudomonas in Anopheles, Ochlerotatus and Aedes may also exclude the presence of Wolbachia in the system, suggesting that bacteria other than Asaia may affect the ability of the system to retain stable Wolbachia infection (Hughes et al, 2014). This is particularly relevant for disease transmission by mosquito vectors, as Wolbachia has been linked to vector competence (e.g., Micieli and Glaser, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the high abundance of Pseudomonas in Anopheles, Ochlerotatus and Aedes may also exclude the presence of Wolbachia in the system, suggesting that bacteria other than Asaia may affect the ability of the system to retain stable Wolbachia infection (Hughes et al, 2014). This is particularly relevant for disease transmission by mosquito vectors, as Wolbachia has been linked to vector competence (e.g., Micieli and Glaser, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The obligate intracellular bacterium Wolbachia pipientis Hertig was first described in the mosquito Culex pipiens Linnaeus and belongs to the order of Rickettsiales (Hertig & Wolbach, ; Hertig, ; Werren, ). In contrast to other members of the Rickettsiales, such as Anaplasma , Ehrlichia and Rickettsia (Werren et al ., ; Micieli & Glaser, ), Wolbachia infects exclusively invertebrate hosts (Werren et al ., , ). Current estimations suggest that at least 40% of terrestrial arthropod species are persistently infected with Wolbachia (Werren et al ., ; Zug & Hammerstein, ).…”
mentioning
confidence: 99%
“…reported that inoculation with the Wolbachia strain wAlbB resulted in an enhancement of WNV infection in Culex tarsalis Coquillett (Dodson et al ., ). Furthermore, WNV resistance in C. quinquefasciatus as well as in C. pipiens seems to depend on Wolbachia density (Micieli & Glaser, ). Thus, not only knowledge about the presence or absence of Wolbachia , but also knowledge about its density might be required to assess the potential for antiviral protection (Moreira et al ., ).…”
mentioning
confidence: 99%
“…While putative difference in protective ability between the w Pip groups identified in Cx. pipiens has not yet been investigated, a general protection by wPip has been shown against West Nile Virus infection (Micieli and Glaser, 2014). To date, no Wolbachia-mediated “protection” against DNA viruses have been shown in any insects.…”
Section: Introductionmentioning
confidence: 99%